The Study of Alternative Internal Standard for Quantitative Analysis of Alum-Contaminated Methamphetamine Hydrochloride by Gas Chromatography - Achalanant, Athip; Seelanan, Parinya (Suan Dusit Graduate School Academic Journal, 2023)
This research aimed to study the efficiency and stability of alternatives Internal Standard (IS) for the quantitative analysis of alum-contaminated Methamphetamine hydrochloride (MA) by Gas Chromatography (GC). The research was performed by the analysis of 4 chemicals including Diphenylamine (DPA), Benzylamine, N-methyl benzylamine and Diphenhydramine as the proposed IS. A mixture of standard MA and alum was prepared and used in this experiment. The results showed that 1) the stability was only achieved by DPA, with no reaction to MA and alum. The prepared DPA as IS in MA analysis can be stored up to 1 month and 2) MA concentration in DPA tested condition was not significantly different to the system without DPA at the statistical significance level of 0.05. It showed that DPA was the efficient IS for quantitative analysis of MA because DPA did not disturb the analysis. In summary, the proposed DPA was exhibited with stability and high efficiency. DPA can be used as an alternative IS for the analysis of alum - contaminated MA with less limitation and difficulty. As the standard method needed sample extraction for elimination of matrixes, use of DPA can reduce the complicated process of extraction. This can encourage a faster analysis with more reliable result for the contaminated drugs under forensic science to the criminal prosecution. Consequently, narcotic examination and inquiry process can be developed for the fairness of justice system.